RANCANG BANGUN SISTEM INFORMASI GEOGRAFIS PENDATAAN INFRASTRUKTUR JALAN BERBASIS ANDROID - Dian Hartanti; Hendarman Lubis; Dwipa Handayani (PETIR, 2018)
Roads are infrastructure that are very important for aspects of human life, because with good roads, road users can safely and comfortably drive, so that it will improve the economic sector in the city, but in reality many roads are currently disrupting. so that road users are not comfortable passing the road when using motorized vehicles, this is caused by changes in shape and texture both in terms of quantity and quality such as damaged or perforated roads, but information about damaged roads cannot be known to many people, especially in the streets remote residential areas of the city, therefore there is a need for geographic information systems to find out information about the availability of roads in the city of Bekasi, to ensure that drivers feel comfortable and safe for their purposes, this system is made using android-based mobile devices that make it easier for users to access anywhere and anytime